Evaluation of Indonesia's Upstream Oil and Gas Fiscal Terms in Comparison to Malaysia's Enhanced Profitability Terms (EPT)Case Study of Block X Exploration Field - Halim, Yosep; Rakhmanto, Pri Agung; Mardiana, Dwi Atty; Irawan, Sonny; Lalaina, Ramefivololona Hanitra; Aimé, Rajomalahy Julien; Fifaliana, Razakamampianina Valisoa; Harifenitra, Ravololoarimanana (Penerbitan Universitas Trisakti, 2025)
Oil and gas sector is one of the main drivers of Indonesia's economy. Thus, it is important to ensure the attractiveness of Indonesia's Production Sharing Contracts (PSC) fiscal terms for investment, especially in comparison with neighboring countries. In 2021, Malaysia introduced the Enhanced Profitability Terms (EPT) PSC, which is considered to provide a better and more reasonable return for oil and gas contractors. The purpose of this study is to analyze and compare the attractiveness of the Cost Recovery and Gross Split fiscal terms in Indonesia with the EPT fiscal terms in Malaysia, based on economic indicators, including their sensitivity. This study uses a quantitative approach by calculating the economic viability of fields (NPV, IRR, POT), their sensitivity, the range of %CT and %GT, and the profitability characteristics of an exploration block field (Block X). From the evaluation and comparison conducted (specific to the assumed case), it was concluded that the Indonesian Gross Split PSC and the Malaysian EPT PSC have improved economic indicators compared to the Indonesian Cost Recovery PSC. Therefore, the Indonesian Gross Split PSC and the Malaysian EPT PSC generally have better economic indicators, including sensitivity to changes in oil prices, operating costs, and production levels, compared to the Indonesian Cost Recovery PSC. To obtain a more complete picture and enrich the evaluation of these fiscal terms, further analysis can be conducted by considering business risks of contractors, simulations with the application of incentives, and other factors that can affect investment decisions.